Aprendizaje cooperativo como estrategia en la resolución de problemas matemáticos en estudiantes de Quinto grado en la I.E.D. Thelma Rosa Areválo (2021)
Problem solving in the area of mathematics has gained relevance in the context, especially because through it the necessary skills to face everyday events are forged. The research aims to implement cooperative learning as a strategy in solving mathematical problems in 5th grade students. The variables were investigated: mathematical problem solving and cooperative learning strategy. The approach is quantitative, empirical-analytical paradigm and quasiexperimental design. There was a sample of 52 students in grade 5 of elementary school from I.E.D Thelma Rosa Arévalo. The pre-test, intervention workshops and post-test were implemented. The results of the post-test evidenced the strengthening of the students' knowledge to analyze and understand mathematical problems. It was concluded that with the cooperative learning strategy and the Pólya methodology, the students became an active agent of their process and not an observer.